Superior piezoelectricity and rhombohedral-orthorhombic-tetragonal phase coexistence of (1 − x)(K, Na)(Nb, Sb)O3−x(Bi, Na)HfO3 ceramics. (February 2020) - Zhang, Jialiang; Sun, Xue; Su, Wenbin; Yao, Weizeng; Zhou, Chunming
Abstract: Requirements for lead-free piezoelectric ceramics are growing increasingly strong owing to environmental concerns. This paper reports the study results of (1 − x )(K0.48 Na0.52 )(Nb0.96 Sb0.04 )O3 – x (Bi0.50 Na0.50 )HfO3 ceramics. It was found that all the ceramics with 0.035 ≤ x ≤ 0.047 show rhombohedral−orthorhombic−tetragonal ( R − O − T ) phase coexistence at room temperature and the one with x = 0.045 has a giant piezoelectric coefficient d 33 of 540 pC/N. Unexpectedly, the rhombohedral−orthorhombic phase transition temperature is almost independent of the (Bi0.50 Na0.50 )HfO3 content. Moreover, electromechanical coupling factor k p is temperature-stable in orthorhombic phase. The results demonstrate that superior piezoelectricity can be obtained in a (K, Na)NbO3 -based ceramic of R − O − T phase coexistence. Graphical abstract: Image, graphical abstract